Psychosocial experiences of caring by family caregivers of patients living with prostate cancer in a teaching hospital: A descriptive phenomenological study - Jerry Paul K. Ninnoni; Benedicta Owoo (Wiley, 2023)
Abstract Aim This study explored the psychosocial experience of caregiving on the family caregiver of patients with prostate cancer in the Cape Coast metropolis of Ghana. Design A descriptive phenomenological study was conducted through in‐depth face‐to‐face semi‐structured interviews. Twelve family caregivers of prostate cancer patients were selected through purposive sampling. Interviews were conducted until data saturation. All interviews were taped, transcribed verbatim and analysed thematically. Results The family caregiver's psychosocial experience associated with caregiving uncovered two significant themes with 13 sub‐themes. 'Psychological impact' emerged as the first central theme, with anxiety, care as an obligation and feelings of inadequacy, hopelessness, uncertainty, denial and concealment as the sub‐themes. The second central theme was 'Social impact' with sexual concerns, role adjustment, loss of livelihood, turmoil and reduced leisure activities emerging as sub‐themes. Conclusion The findings demonstrated that caring significantly impacts the psychological and social well‐being of the caregivers of prostate cancer patients. Therefore, there is a need for holistic assessment to include the psychosocial well‐being of family caregivers to improve quality of life. Therefore, psychiatric nurses support family caregivers through education and psychosocial interventions to improve their quality of life and enable them to care for their loved ones more effectively.